Genome-wide analysis of the WOX gene family and function exploration of RhWOX331 in rose (R. ‘The Fairy’) - Duan, Lian; Hou, Zhihui; Zhang, Wuhua; Liang, Shuang; Huangfu, Minge; Zhang, Jinzhu; Yang, Tao; Dong, Jie; Che, Daidi (Frontiers in Plant Science, 2024)
WOXs are a class of plant-specific transcription factors that play key roles in plant growth and stress responses. However, the mechanism by which WOXs influence adventitious root development in Rosa hybrida remains unclear. In this study, RcWOX gene family in rose was identified and phylogenetically analyzed. A total of 381 RcWOX gene members were localized on seven chromosomes except of nine members. The main cis-acting elements involved in hormonal, light, developmental, and abiotic stress responses were identified in the promoters of RcWOX genes, suggesting their regulation by these signals. Nine RhWOX genes had significant different expression during rooting process of rose. RhWOX331, RhWOX308, RhWOX318 were positive with the formation of rose roots. RhWOX331 was positively involved in the formation of adventitious root primordia, which gene coding a transcription factor localized in the nucleus. The HOX conserved domain in the protein contributed to the selfactivating activity of RhWOX331. Overexpression of RhWOX331 gene alleviated the inhibition of root length of A. thaliana primary roots by high concentration of IBA and NPA, and significantly increased the number of lateral roots on the primary roots, as well as the height of A. thaliana plants. Additionally, RhWOX331 promoted adventitious root formation in A. thaliana and mitigated hormonal inhibition by exogenous 6-BA, NPA, and GA3. The RhWOX331 promoter contained cis-acting elements such as ABRE, Box 4 and CGTCA-motif et.al. GUS activity analysis showed that the gene acted at the cotyledon attachment site. Taken together, these studies identified a significant expansion of the RcWOX gene family, inferred roles of certain branch members in adventitious root formation, elucidated the function of RhWOX331 in adventitious root initiation, and laid the foundation for further research on the function of WOX gene family in roses.